2008
DOI: 10.1074/jbc.m805138200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Protein Tyrosine Phosphatase Shp-2 Is One Important Negative Regulator of Nuclear Export of Telomerase Reverse Transcriptase

Abstract: Aging is one major risk factor for numerous diseases. The enzyme telomerase reverse transcriptase (TERT) plays an important role for aging and apoptosis. Previously, we demonstrated that inhibition of oxidative stress-induced Src kinase family-dependent nuclear export of TERT results in delayed replicative senescence and reduced apoptosis sensitivity. Therefore, the aim of this study was to investigate mechanisms inhibiting nuclear export of TERT. First, we demonstrated that H 2 O 2 -induced nuclear export of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 40 publications
3
66
0
Order By: Relevance
“…However, studies in other tissues, such as endothelial cell cultures or 293T cells, have found that C459S does indeed exert dominant-negative effects in those systems (13,38,39). Therefore, loss of dominance in the C459S-Q510E double mutant is, in our opinion, an unlikely explanation.…”
Section: Discussionmentioning
confidence: 73%
“…However, studies in other tissues, such as endothelial cell cultures or 293T cells, have found that C459S does indeed exert dominant-negative effects in those systems (13,38,39). Therefore, loss of dominance in the C459S-Q510E double mutant is, in our opinion, an unlikely explanation.…”
Section: Discussionmentioning
confidence: 73%
“…The function of nuclear SHP-2 in prostate cancer could be involved in migration and invasion since nuclear expression correlated with extracapsular extension of the cancer. Prior studies have also reported SHP-2 in the nucleus [16][17][18][19]. Since SHP-2 lacks a typical nuclear localization signal sequence, it could be transported to the nucleus in association with proteins such as Gab1 [19].…”
Section: Correlation Of Shp-2 With Clinicopathological Parameters Andmentioning
confidence: 94%
“…Prior studies have also reported SHP-2 in the nucleus [16][17][18][19]. Since SHP-2 lacks a typical nuclear localization signal sequence, it could be transported to the nucleus in association with proteins such as Gab1 [19]. Although it remains unclear, differential compartmentalization may alter SHP-2 function.…”
Section: Correlation Of Shp-2 With Clinicopathological Parameters Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Thirty minutes later, SNO-SHP-2 formation was detected by the biotin-switch assay. Old SNOC and GSH were controls in the absence of an NO donor; without methyl methanethiosulfonate (MMTS; without the free thiol blocker) and without N- [6- negative (34), failed to protect neurons from NMDA toxicity. These data suggest that rescue of cortical neurons by SHP-2 expression requires its catalytic activity and that S-nitrosylation of SHP-2 might inhibit the neuroprotective pathway.…”
Section: S-nitrosylation Of Shp-2 Suppresses Its Phosphatase Activitymentioning
confidence: 99%